Graph x^2+y^2-6x-2y-9=0

Math
x2+y2-6x-2y-9=0
Add 9 to both sides of the equation.
x2+y2-6x-2y=9
Complete the square for x2-6x.
Tap for more steps…
Use the form ax2+bx+c, to find the values of a, b, and c.
a=1,b=-6,c=0
Consider the vertex form of a parabola.
a(x+d)2+e
Substitute the values of a and b into the formula d=b2a.
d=-62(1)
Simplify the right side.
Tap for more steps…
Cancel the common factor of 6 and 2.
Tap for more steps…
Factor 2 out of 6.
d=-2⋅32⋅1
Cancel the common factors.
Tap for more steps…
Factor 2 out of 2⋅1.
d=-2⋅32(1)
Cancel the common factor.
d=-2⋅32⋅1
Rewrite the expression.
d=-31
Divide 3 by 1.
d=-1⋅3
d=-1⋅3
d=-1⋅3
Multiply -1 by 3.
d=-3
d=-3
Find the value of e using the formula e=c-b24a.
Tap for more steps…
Simplify each term.
Tap for more steps…
Raise -6 to the power of 2.
e=0-364⋅1
Multiply 4 by 1.
e=0-364
Divide 36 by 4.
e=0-1⋅9
Multiply -1 by 9.
e=0-9
e=0-9
Subtract 9 from 0.
e=-9
e=-9
Substitute the values of a, d, and e into the vertex form a(x+d)2+e.
(x-3)2-9
(x-3)2-9
Substitute (x-3)2-9 for x2-6x in the equation x2+y2-6x-2y=9.
(x-3)2-9+y2-2y=9
Move -9 to the right side of the equation by adding 9 to both sides.
(x-3)2+y2-2y=9+9
Complete the square for y2-2y.
Tap for more steps…
Use the form ax2+bx+c, to find the values of a, b, and c.
a=1,b=-2,c=0
Consider the vertex form of a parabola.
a(x+d)2+e
Substitute the values of a and b into the formula d=b2a.
d=-22(1)
Simplify the right side.
Tap for more steps…
Cancel the common factor of 2.
Tap for more steps…
Cancel the common factor.
d=-22⋅1
Divide 1 by 1.
d=-1⋅1
d=-1⋅1
Multiply -1 by 1.
d=-1
d=-1
Find the value of e using the formula e=c-b24a.
Tap for more steps…
Simplify each term.
Tap for more steps…
Raise -2 to the power of 2.
e=0-44⋅1
Multiply 4 by 1.
e=0-44
Divide 4 by 4.
e=0-1⋅1
Multiply -1 by 1.
e=0-1
e=0-1
Subtract 1 from 0.
e=-1
e=-1
Substitute the values of a, d, and e into the vertex form a(x+d)2+e.
(y-1)2-1
(y-1)2-1
Substitute (y-1)2-1 for y2-2y in the equation x2+y2-6x-2y=9.
(x-3)2+(y-1)2-1=9+9
Move -1 to the right side of the equation by adding 1 to both sides.
(x-3)2+(y-1)2=9+9+1
Simplify 9+9+1.
Tap for more steps…
Add 9 and 9.
(x-3)2+(y-1)2=18+1
Add 18 and 1.
(x-3)2+(y-1)2=19
(x-3)2+(y-1)2=19
This is the form of a circle. Use this form to determine the center and radius of the circle.
(x-h)2+(y-k)2=r2
Match the values in this circle to those of the standard form. The variable r represents the radius of the circle, h represents the x-offset from the origin, and k represents the y-offset from origin.
r=19
h=3
k=1
The center of the circle is found at (h,k).
Center: (3,1)
These values represent the important values for graphing and analyzing a circle.
Center: (3,1)
Radius: 19
Graph x^2+y^2-6x-2y-9=0

Download our
App from the store

Create a High Performed UI/UX Design from a Silicon Valley.

Scroll to top